DEVELOPING INFOGRAPHICS OF CAKEAPP BASED TEACHING SPEAKING IDEAS FOR TOURISM VOCATIONAL HIGH SCHOOL ENGLISH TEACHER IN 11th GRADE AT SMK NEGERI 2 SINGARAJA - Yasa, Gede Amerta; Utami, IGA Lokita Purnamika; Agustini, Dewa Ayu Eka (Lingua Scientia, 2024)
This research aims to develop infographics based teaching speaking ideas for Tourism Vocational High School English teacher in 11th grade, odd semester at SMK Negeri 2 Singaraja. The Design and Development research by Richey and Klein (2014) was involved in this research as the foundation with DDE as research steps. DDE stands for the design, development, and evaluation stage in order to develop  and determine the quality of infographics based teaching speaking ideas. The data collection procedure in this research used several instruments, namely, observation sheet, interview guides, document analysis (syllabus analysis, and blueprint of infographic). Meanwhile, the other instruments were used to evaluate the infographics in the form of content and product judgment validation, infographic refinement sheet. The data was analyzed through descriptive qualitative method. This research involved the syllabus analysis and needs analysis that will be considered in designing and developing an innovative IDT (Instructional Design and Technology) product for ESP (English for Specific Purposes) teachers, especially in teaching speaking skills in Tourism Vocational High School at SMK Negeri 2 Singaraja. In order to measure the product quality, the researcher used content and product expert judgment adapted from Findawati and Suprianto (2014). The quality of  the infographics was assessed through content validity testing using Gregory Formula (Gregory, 2007) and Likert scale. The research validity test results show that the infographics are suitable for the learning needs in the ESP context with relevant teaching speaking ideas and as good digital learning tools.